2010
DOI: 10.1111/j.1365-277x.2010.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary adequacy in a remote Inuvialuit population

Abstract: Background:  Traditional foods are rich sources of essential nutrients, but Inuvialuit in the Northwest Territories (NWT), Canada, have been undergoing a nutrition transition, characterised by an increased consumption of non‐nutrient‐dense foods. The present study aimed to characterise energy, nutrient and food intakes amongst adult Inuvialuit. Methods:  The study collected up to three 24‐h dietary recalls on nonconsecutive days for each participant in spring/summer of 2008 in one remote community in the NWT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 19 publications
(22 reference statements)
4
40
0
Order By: Relevance
“…Because of their high sugars and/or fat content (especially saturated fats), consumption of these foods is undesirable and could lead to obesity. Previous studies (Erber et al 2010b) have shown that NNDFs make a large contribution to energy intake in this population. As an example of the difference between NNDFs and traditional meats in terms of nutritional composition, pepperoni pizza per 100 g has 296 kcal, 11.2 g protein, 15.2 g fat, 46.3% of calories from fat, 0.57 mg vitamin B12 and 2.4 mg iron (Lawn and Harvey 2003), whereas roasted caribou per 100 g has 142.5 kcal, 27.3 g protein, 2.8 g fat, 19.0% of calories from total fat, 6.5 mg vitamin B12 and 5.2 mg iron (Canadian Nutrient File 2011).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because of their high sugars and/or fat content (especially saturated fats), consumption of these foods is undesirable and could lead to obesity. Previous studies (Erber et al 2010b) have shown that NNDFs make a large contribution to energy intake in this population. As an example of the difference between NNDFs and traditional meats in terms of nutritional composition, pepperoni pizza per 100 g has 296 kcal, 11.2 g protein, 15.2 g fat, 46.3% of calories from fat, 0.57 mg vitamin B12 and 2.4 mg iron (Lawn and Harvey 2003), whereas roasted caribou per 100 g has 142.5 kcal, 27.3 g protein, 2.8 g fat, 19.0% of calories from total fat, 6.5 mg vitamin B12 and 5.2 mg iron (Canadian Nutrient File 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies among Arctic indigenous peoples have shown that there have been consistent increases in the consumption of nonnutrient-dense foods (NNDFs), such as processed meats, sugary beverages and chips, and that these foods have become the predominant foods in indigenous peoples' diets compared with traditional foods (Kuhnlein and Receveur 1996;Receveur et al 1997;Kuhnlein et al 2004;Erber et al 2010aErber et al , 2010b. However, up-to-date information on such eating patterns among Inuvialuit is lacking.…”
Section: Introductionmentioning
confidence: 95%
“…Briefly, despite contamination by POPs, the traditional diet is widely accepted to be the healthiest diet available to indigenous peoples of the Arctic. The transition to nutrient-poor store bought foods is associated with inadequate intake of micronutrients, while a traditional diet tends to increase consumption of micronutrients and decrease intake of sugar carbohydrates and fat (Kuhnlein et al 2004; Bersamin et al 2007; Erber et al 2010; Hopping et al 2010). Further, high intake of omega-3 fatty acids in subsistence diets may be protective against metabolic syndrome and obesity related diseases, although not protective against cancer (Ebbesson et al 2005; Makhoul et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Here evolutionary forces have provided human populations an alternative source of vitamin D in the form of oily fi sh (salmon and whale blubber) that could easily satisfy vitamin D requirements. Deviation from these traditional dietary sources of vitamin D leads to vitamin D de fi ciency and reduced fetal viability [65][66][67][68][69][70][71][72] .…”
Section: Uvb Light Exposure and Vitamin D Levels And Control Of Skin mentioning
confidence: 99%